Revelation of intertwining organic and inorganic fractal structures in polymer coatings - Hughes, A E (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.